Coronary artery ectasia: prevalence, angiographic characteristics and clinical outcome. Issue 1 (6th April 2020) - Willner, Nadav Asher; Ehrenberg, Scott; Musallam, Anees; Roguin, Ariel
Abstract : Objective: Determine coronary artery ectasia (CAE) prevalence and clinical outcome in a large cohort of patients underwent coronary angiography. Methods: In an 11-year period, between 2006 and 2017, 20 455 coronary angiography studies were performed at a large university centre. Patients diagnosed with CAE based on procedure report were included in the final analysis. Results: CAE was diagnosed in 174 out of 20 455 studies (0.85% per total angiograms, 161 patients). Patients' average age was 59.6±11.2 years old with male predominance (90.7%). Diffuse ectasia morphology was most common (78.9%), followed by fusiform (16.1%) and saccular (5%). Mixed CAE and atherosclerotic heart disease (ASHD) was present in 75.2% of the patients and isolated CAE in 24.8%. The most common coronary artery involved was the right coronary artery (RCA) (79%). Following index angiography, all the isolated CAE group was managed conservatively, while 67% of the mixed CAE-ASHD group underwent coronary intervention. In an average follow-up of 6±3.6 years, adverse clinical event (a composite endpoint of any death, cerebrovascular accident, myocardial infarction, thromboembolic event, bleeding and stent thrombosis) occurred in 48.8% of the mixed CAE-ASHD group compared with 25% in the isolated CAE group (p<0.05). Conclusions: CAE is a rare phenomenon. The most common artery involved was the RCA, and the diffused type of CAE was the most frequent. Most patients with CAE have also concomitant ASHD, and those patients have higher mortality and complications rate, compared with isolated CAE disease.